PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP CUSTOMER DELIGHT MELALUI CUSTOMER SATISFACTION - Putri, Husni Indrawati Wijaya (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2019)
The objective of this research is to analyze the influence of service quality dimensions which consist of tangibles; reliability; responsiveness; assurance; and empathy on customer delight through customer satisfaction. The research sample was the students of the Faculty of Economics and Business, Study Program of Management, University of Wijaya Kusuma Surabaya batch of 2016/2017 that consisted of 90 respondents. The data analysis technique used was path analysis. The results showed that the dimensions of service quality, i.e., tangibles, reliability, responsiveness, assurance, and empathy affect customer delight as mediated by customer satisfaction.